Service Quality, Its Importance in Marketing and Competitive Strategies - Budiyono, Snehal Pawar-Hole, Yogesh Hole, Vishal Wagh (International Journal of Control and Automation, 2020)
The development of a modern competitive environment and those of information technology through globalization has encouraged companies to focus more on the context of Service quality. These service qualitiesshould be especially oriented toward customer satisfaction and that of the aspects associated with those of customer loyalty, its effect on increasing the revenue. In the era of customers,they are in search of the companies who provide good service, this is one of the most important strategies for their organizational success and satisfies the urge of survival in today's competitive environment. The methodology of critical value analysis is put into use for the setting of the customer service according to their priorities. Furthermore, an approach is being undertaken to evaluate the importance of the customers is also adopted. This research paper ends with an appropriate conclusion that discusses the relevant findings of the survey and proposes a way to conduct more research in the future. The main purpose of this research paper is to develop a contextual understanding of the subject and to examine in a better way the relationship that lies in between the aspect of the service quality (SQ), the context of the satisfaction or CS and that of the customer loyalty (CL). All the mentioned aspects are instrumental in leadinga company toward competitiveness advantages.